Analysis of Employee Performance Through The Role of Knowledge Sharing and Competence With Commitment as Intervening Variables - Yoga Dwi Anugrahadi; Gendut Sukarno; Ika Korika Swasti (Jurnal Manajemen Bisnis, 2023)
The primary objective of this analysis is to ascertain the influence of information sharing and competency on employee performance within the context of the Department of Public Works and Highways Water Resources in Sidoarjo Regency. The study's target population consists of individuals employed in general or executive functional roles. The sample methodology utilised in this study involves the use of non-probability sampling, specifically employing a purposive sampling technique. The sample consisted of a total of 77 individuals. The data was derived from primary sources. Simultaneously, the study employs the Partial Least Squares (PLS) method. The findings of the study suggest that there is a noteworthy positive relationship between knowledge sharing and commitment. Conversely, competence is found to have a significant negative influence on commitment. Additionally, knowledge sharing is found to have a positive impact on employee performance, while competence does not have a significant effect on employee performance. Moreover, commitment is found to have a positive influence on employee performance. Furthermore, commitment is identified as a mediating factor in the relationship between knowledge sharing and employee performance, but it does not mediate the effect of competence on employee performance.